Effects of FlAsH/Tetracysteine (TC) tag on PrP proteolysis and PrPres formation by TC-scanning - Taguchi, Yuzuru (2013)
The FlAsH/tetracysteine (FlAsH/TC) tag is a powerful tool for fluorescent labeling of proteins. However, even small tags such as FlAsH/TC could alter the behavior of the tagged proteins, especially if the insertion occurs at internal sites. Defining the influence of FlAsH/TC on nearby protein-protein interactions might aid in selecting appropriate positions for internal TC insertions and allow the exploitation of serial FlAsH/TC insertions (TC-scanning) as a probe to characterize sites of protein-protein interaction. To explore this application in the context of substrate-protease interactions, we analyzed the effect of FlAsH/TC insertions on proteolysis of cellular prion protein (PrPsen) in in vitro reactions and generation of the C1 metabolic fragment of PrPsen in live neuroblastoma cells. The influence of FlAsH/TC insertion was evaluated by TC-scanning across the cleavage sites of each protease. The results showed that FlAsH/TC inhibited protease cleavage only within limited ranges of the cleavage sites that varied from about 1 to 6 residues-wide depending on the protease, providing an estimate of the PrP residues interacting with each protease. TC-scanning was also used to probe a different type of protein-protein interaction, the conformational conversion of FlAsH-PrPsen to the prion disease-associated isoform, PrPres. PrP constructs with FlAsH/TC insertions at residues 90–96 but not 97–101 were converted to FlAsH-PrPres, identifying a boundary separating loosely versus compactly folded regions of PrPres. Our observations demonstrate that TC-scanning with the FlAsH/TC tag can be a versatile method for probing protein-protein interactions and folding processes.